2014
DOI: 10.1016/j.bbmt.2014.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Measurement of Liver Fibrosis Using Transient Elastography in Pediatric Patients with Major Thalassemia Who Are Candidates for Hematopoietic Stem Cell Transplantation

Abstract: Although liver biopsy is an invasive procedure, it remains the gold standard technique for the evaluation of hepatic fibrosis in different patients, including those with major thalassemia (MT). Recently, noninvasive imaging techniques, such as transient elastography, have emerged. We investigated the effectiveness of TE, in comparison to liver biopsy, for the evaluation of liver fibrosis in pediatric patients with MT who were candidates for hematopoietic stem cell transplantation (HSCT). Eighty-three pediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Eight studies did not find any effect of age (19,23,24,31,37,(43)(44)(45). Success rates were lower in younger children (14,19,21,23,43,44).…”
Section: Age Gender Bmi and Necro-inflammatory Gradementioning
confidence: 85%
See 1 more Smart Citation
“…Eight studies did not find any effect of age (19,23,24,31,37,(43)(44)(45). Success rates were lower in younger children (14,19,21,23,43,44).…”
Section: Age Gender Bmi and Necro-inflammatory Gradementioning
confidence: 85%
“…Boys had higher liver stiffness values compared with girls in two studies (21,45), but in six studies gender had no effect on measurements (19,22,23,37,41,42). BMI did not influence liver stiffness in four studies (22,24,31,41), while a high BMI lead to unsuccessful measurement in other studies (23,34,37). Increasing necroinflammatory grade was correlated to increasing liver stiffness in two studies (24,25).…”
Section: Age Gender Bmi and Necro-inflammatory Gradementioning
confidence: 93%
“…It is becoming an attractive technology for assessment of liver fibrosis as it is readily available, non-invasive, accurate, low cost, reproducible, and suitable for use in a variety of clinical settings. There are limited data about the role of Transient Elastography (TE) in the assessment of liver fibrosis in patients with TM and no data on the utility of the 2-D SWE imaging technique in such cases [10][11][12][13]. Therefore, the present study aimed to stage liver fibrosis in patients with TM using the 2-D SWE imaging technique in staging hepatic fibrosis and evaluating risk factors associated with significant fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, we had previously demonstrated the correlation of transient elastography with histological measure of hepatic iron deposition. 2 , 19 , 20 Therefore, we used the liver stiffness as an indirect measure of both liver fibrosis and liver iron deposit. We demonstrated that plasma level of Gpx was inversely associated with HBV DNA count and liver stiffness whereas serum iron was positively associated with HBV DNA count and was indirectly affecting the liver stiffness.…”
Section: Discussionmentioning
confidence: 99%